Discovering the Impact of ICT, FDI and Human Capital on GDP: A Cross-sectional Analysis. (27th September 2013) - Campisi, Domenico; De Nicola, Arianna; Farhadi, Maryam; Mancuso, Paolo
This paper investigates the impact that human capital, information and communication technology (ICT) and foreign direct investment (FDI) have on GDP. Cross-sectional data from a set of 20 OECD and 24 non-OECD countries in 2007 are analysed employing data envelopment analysis (DEA) and classification and regression tree (CART) techniques. The paper illustrates that the level and quality of access to ICT infrastructures plays an important role in determining a country's level of technical efficiency. The paper also indicates the presence of a catch-up process, led by technological innovation, on the part of emerging countries.